On the use of HDDR powder from Nd-Fe-B End-of-Life magnets as raw material for laser powder bed fusion - Fertig, Bruno Lessmann (2024)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência e Engenharia de Materiais, Florianópolis, 2024.